Analisis Hubungan Budaya Organisasi, Komitmen Organisasi dengan Turnover Intention Perawat Rumah Sakit Prikasih Tahun 2015 - Rahmawati, Erta (UI Scholars Hub, 2016)
The high rate of nurse turnover > 10% at Prikasih hospital causes a variety of problems, increased operating cost, disruption operations and raising moral issues in nurse who stay, This research is a quantitative analytical research aiming to describe the types of organizational culture (clan, adhocracy, market, hierarchy) and organizational commitment (affective, normative, continuance). The research also aims to illustrate the relations between the different types of organizational culture and organizational commitment, and the association with turnover intention at Prikasih hospital as well as to identify the most dominant factor of relations. The research uses cross-sectional method with 102 nurses as respondents, using questionnaires. The result correlation and regresion analysis shows that there is correlation between organizational culture (clan, market, hierarchy), organizational commitment (affective, normative, continuance) with turnover intention. Affective commitment exhibits as the most dominant variable in relation to turnover intention.